Real world outcomes in patients with neuroendocrine tumor receiving peptide receptor radionucleotide therapy - Stijn Hentzen; Kathan Mehta; Raed Moh'd Taiseer Al-Rajabi; Anwaar Saeed; Joaquina Celebre Baranda; Stephen K. Williamson; Weijing Sun; Anup Kasi (Open Exploration Publishing Inc., 2023)
Aim: 177Lu-Dotatate (Lu-177), a form of peptide receptor radionuclide therapy (PRRT), was approved by Food and Drug Administration (FDA) for the treatment of somatostatin-receptor-positive neuroendocrine tumors (NETs) in 2018. Clinical trials prior to the FDA approval of Lu-177 showed favorable outcomes but there is limited published real world outcomes data. This study aims to describe and analyze real world outcomes of patients with NET who received Lu-177. Methods: After obtaining institutional review board approval, retrospective evaluation was performed to analyze the efficacy of Lu-177 for somatostatin receptor-positive gastro-entero-pancreatic NETs (GEP-NETs) patients at the University of Kansas Cancer Center between June 2018 and September 2021. This study aims to determine the response rate to the treatment of the entire cohort and subgroups. Results: A total of 65 patients received Lu-177 of which 58 completed treatment. The 58 patients had a median age of 61.5 years, 24 females and 34 males, 86% Caucasian and 12% black. The origins of NETs were primarily small bowel (n = 24) and pancreatic (n = 14). Pathology showed grades 1 (n = 21), 2 (n = 25), and 3 (n = 4) and were primarily well-differentiated tumors (n = 4). Among the cohort, 52 patients had imaging to assess response with 14 (26.9%) patients with partial response (PR), 31 (59.6%) with stable disease (SD), and 7 (13.5%) with progressive disease (PD). In a subset analysis, patients with non-functional disease (n = 29) had higher rates of PR 42.3% (compared to 11.5%, P = 0.0147) and higher disease control rate of 96% (compared to 78%, P = 0.042) than patients with functional disease (n = 29). Patients with non-functional disease had a lower PD of 3.85% (compared to 23%, P = 0.0147) than those with functional disease. Conclusions: This real world outcomes analysis of NETs treated with Lu-177 shows improved PR when compared to the initial clinical trials and is promising for patients. In addition, patients with non-functional tumors were found to have a statistically significant improved response rate which has not been described in the literature before. If these study findings are validated in a larger cohort they may guide patient selection for Lu-177 therapy in the future.